Self-Insurance and Self-Protection as Public Goods - Tim Lohse; Julio R. Robledo; Ulrich Schmidt (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
Many public goods like dams, fire departments, and lighthouses do not provide direct utility but act more as insurance devices against floods, fire, and shipwreck. They either diminish the probability or the size of the loss. We extend the public good model with this insurance aspect and generalize Samuelson?s efficient allocation rule when self-insurance and self-protection expenditures are pure public goods. Some comparative static results with respect to changes in income and risk behavior are derived. As some of the sketched risks are insurable while some others are not, we introduce further the possibility of risk coverage by private market insurance. We analyze the interaction of such an insurance with the public good level, both for efficient provision and for private provision equilibria. It turns out that the levels of self-insurance and self-protection decrease when being privately provided. Moreover, it appears a strategic substitutability between the public good and market insurance which leads to an additional decline of the provision levels.
Keywords: H41; G22; 330; Self-insurance; self-protection; efficient provision of public goods; private provision of public goods; market insurance; Öffentliches Gut; Allokationseffizienz; Versicherungsökonomik; Brandschutz; Schiffssicherheit; Theorie